Can US Coordination Failure Explain Why Americans Work So Much More than Europeans? - Maurice Schiff (Institute for the Study of Labor (IZA), 2014)
Prescott (2004) argues that Europeans work much less than Americans because of higher taxes and that they would gain significantly by charging US taxes and working as much as Americans. I argue that the opposite may be true and that Americans work more than Europeans due to a coordination failure. Studies show that utility falls with other people's income, a negative externality that is internalized in Europe through laws on the minimum amount of vacation time (and maximum hours of work), something unthinkable in the US. Thus, Americans may be stuck in an overworking trap and would gain by working less. A simple model and data on work time are used to obtain an estimate of the US welfare gain from reducing its work time to Europe's level. On the other hand, if neither EU nor US work time is optimal, then the sign of the EU-to-US welfare difference is positive (ambiguous) if EU work time is greater (smaller) than the optimum, while simulations show that even in the latter case, EU welfare is greater than US welfare if, relative to the optimum, the EU work 'shortage' is smaller than the US work 'surplus'.
Keywords: D70; J22; 330; work; leisure; Europe; US coordination failure